Development and characterization of hyaluronic acid-lysine nanoparticles with potential as innovative dermal filling - Jaqueline Carneiro; Patrícia Mathias Döll-Boscardin; Bárbara Celânia Fiorin; Jessica Mendes Nadal; Paulo Vitor Farago; Josiane Padilha de Paula
ABSTRACT Skin aging causes changes such as wrinkles and flaccidity leading to a large demand for aesthetic procedures, including dermal filling. A key agent in dermal filling is hyaluronic acid (HA), which is a naturally occurring glycosaminoglycan. However, it is a hydrophilic macromolecule that experiences great difficulty in crossing the skin barrier causing most commercial formulations containing it to be injectable, which in turn brings risks since they involve an invasive technique. In that sense, the aim of this study was to develop and characterize nanoparticles obtained from ionic interaction between HA and lysine (Lys) for use as a potential agent of dermal filling for topical application, increasing and improving its applicability and safety. To this end, nanoparticles were obtained by dripping of Lys over HA under magnetic stirring. A nanometric size was confirmed and a suitable surface charge was obtained by zeta potential. Nanoparticles were almost spherical in shape with a smooth surface. Interaction between raw materials for preparing nanoparticles was studied by FTIR and NMR spectroscopy and an ionic interaction was confirmed. These physicochemical features suggest that obtained nanoparticles can be further used as a topical dermal filling.